Hidrólise enzimática do amido do mesocarpo de babaçu (Attalea speciosa) para produção de bebida alcoólica destilada - CRUZ , Neurene da (2021)
In the North and Northeast of Brazil there is an area called cocais area where there are babassu, palm species, which are used in the manufacture of household utensils and edible products such as pulp, flour and vegetable oil. This palm is known as babassu, has scientific name Attalea speciosa, is one of native species, which stands out in the Northeast region, mainly in the state of Maranhão. Its fruit is known as babassu coconut and is composed of the parts: epicarp, mesocarp, endocarp and almonds, among which stands out the mesocarp that has still little explored potential. The study of babassu mesocarp biomass, with a view to its application in the production of bioproducts, is strategic and of fundamental economic and social importance, since it can add greater commercial value to this natural resource and can increase the economy of some communities where it exists abundance of that feature. In this study, the chemical composition of the babassu mesocarp was characterized and from this biomass an alcoholic beverage was produced by enzymatic hydrolysis, using commercial enzymes and also by saccharification and simultaneous fermentation with the use of fungi. The biomass characterization confirms a high percentage starch, the most abundant component of mesocarp flour. This work also isolated and identified fungi from the environment grown in manioc flour beijus collected in a tiquira still in the municipality of Urbano Santos-Maranhão and babassu mesocarp flour. The enzymatic index of the fungi was also analyzed.